2017
DOI: 10.1002/widm.1231
|View full text |Cite
|
Sign up to set email alerts
|

An overview of emerging pattern mining in supervised descriptive rule discovery: taxonomy, empirical study, trends, and prospects

Abstract: Emerging pattern mining is a data mining task that aims to discover discriminative patterns, which can describe emerging behavior with respect to a property of interest. In recent years, the description of datasets has become an interesting field due to the easy acquisition of knowledge by the experts. In this review, we will focus on the descriptive point of view of the task. We collect the existing approaches that have been proposed in the literature and group them together in a taxonomy in order to obtain a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 66 publications
(67 reference statements)
0
30
0
Order By: Relevance
“…EPM is a data mining task for searching patterns whose support significantly differs between two classes or databases [7,8]. A pattern is considered as emerging if and only if its growth rate (GR) is larger than a given threshold ρ > 1.…”
Section: Emerging Pattern Miningmentioning
confidence: 99%
See 4 more Smart Citations
“…EPM is a data mining task for searching patterns whose support significantly differs between two classes or databases [7,8]. A pattern is considered as emerging if and only if its growth rate (GR) is larger than a given threshold ρ > 1.…”
Section: Emerging Pattern Miningmentioning
confidence: 99%
“…These can be classified according to the approach used to mine the emerging patterns (EPs). A complete review of these approaches can be found in [8]. Nevertheless, the majority of the algorithms developed along the literature has been focused on classification purposes.…”
Section: Emerging Pattern Miningmentioning
confidence: 99%
See 3 more Smart Citations